Foreign Direct Investment Statistics : How Countries Measure FDI 2001. (International Monetary Fund, 2003)
International standards for measuring foreign direct investment (FDI) have become important in today's global economy, where multinational enterprises exercise economic clout and FDI statistics can reflect investor sentiment about the climate of investment in a country. This joint IMF/OECD report assesses progress toward standardization in the compilation of FDI statistics and provides information on statistical methodologies in 61 countries. The report is based on data from the 2001 update of the joint IMF/OECD Survey of Implementation of Methodological Standards for Direct Investment (SIMSDI), which covers 30 OECD countries and 31 other IMF member countries.